Ecodry luxe - Asraf, Khairul Imran; Ruhaizam, Azizir Razi; Anne, Catherine; Abd Aziz, Najdah (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
EcoDry Luxe is a multipurpose and innovative shoe rack designed to address common challenges in shoe care, such as wetness, bacteria buildup, odors, and limited functionality. This product combines advanced features, including a steam drying system, UV-light sanitization, automated deodorant spray, airflow system, and a sock hanging compartment, to ensure shoes remain dry, hygienic, and odor-free. The idea for EcoDry Luxe emerged from the need for a more effective, convenient, and eco-friendly solution to traditional shoe racks, which often fail to tackle issues like mold and musty smells. By integrating sustainable design with advanced technology, EcoDry Luxe provides a complete solution for maintaining footwear. The product’s uniqueness lies in its combination of hygiene-focused features and added conveniences, such as a wireless charging port, lightweight portability, and energy-saving eco mode. EcoDry Luxe reduces the reliance on excessive energy and chemical deodorizers, contributing to a healthier environment. This innovation has a strong commercialization prospect, targeting households, athletes, and professionals who value hygiene and convenience. Its potential impact includes improving shoe longevity, reducing waste, and promoting sustainable living. EcoDry Luxe is not only a practical household item but also a step forward in addressing socio-environmental concerns through efficient and eco-conscious design.